RESPONSIBILITY of WALKING TOWARDS PERFECTION - Halima Yuldasheva (Journals Park Publishing, 2024)
The article analyzes the issues of traditioh and literary successionin Uzbek classical literature on the example of Erkin Vahidov. In Erkin Vahidov’s poetry, the traditionalism of the individual and society is studied on the basis of the poet’s work and classical poetry.
Keywords: poetry, national spirit, criticizm of virtues, vices, artistic interpretation.